ALTERNATIVE TREE CROPS FOR RECONSTRUCTION OF THE GREEN INFRASTRUCTURE POST-TSUNAMI IN THE COASTAL AREAS OF ACEH BARAT DISTRICT - Wahyunto Wahyunto; Sofyan Ritung; Wahyu Wahdini; Fahmuddin Agus (Indonesian Agency for Agricultural Research and Development, 2009)
Tree farming such as coconut, cocoa, coffee, rubber, and rambutan was dominant in the west coast of Aceh prior to tsunami. The farming is not only important for sustainable livelihood, but also for superior environmental protection. During the tsunami, considerable portion of this ‘green infrastructure’ was devastated. Therefore, a scientifically based land suitability evaluation is needed for supporting the redesign and reconstruction of the tree-based farming. The objectives of this research were to evaluate the current physical condition of the area and develop recommendation of land suitability for tree crops farming in the area. Field survey for inventory and evaluation of land characteristics was conducted in 2006, 15 months after the tsunami. Land suitability evaluation was conducted by matching field survey data and soil sample analyses in every mapping unit with crop growth requirements. The land suitability map was further matched with the district development plan, existing land uses and land status. The resulted land use recommendation map showed that the marine ecosystem along the coastal line was most suitable for coconut, cacao, coffee, and casuarinas. The recommended tree crops for the ancient sandy beach were areca nut, coconut, rambutan, mango, rubber and oil palm; and for the alluvial ecosystem were coconut, cacao, areca nut, mango, and bread fruit. Peatland of less than 3 m thick was marginally suitable for oil palm and rubber, while those thicker than 3 m were recommended for conservation due to its fragile ecosystem. In the undulating tectonic plain, the suitable tree crops were rubber, oil palm, coconut, and rambutan.